Can CBDCs reinforce national control over public finance without risk? - S. Yash Kalash (Centre for International Governance Innovation (CIGI), 2025)
Protecting fiscal sovereignty (the ability to independently manage and control public assets) is a key concern for many countries in a rapidly evolving digital financial landscape. Central bank digital currencies (CBDCs), which are government-issued digital money, may be the solution to maintain national control over public finance without the risk of systemic or political fallout. Factors such as dollarization, capital mobility and institutional constraints have undermined fiscal autonomy, especially in emerging and developing economies. CBDCs can address these concerns by improving governments' fiscal transparency through real-time expenditure monitoring, programmable transfers and other tools. But CBDCs are not entirely risk-free and require regulatory supervision to mitigate privacy concerns and ensure institutional readiness.
Keywords: 330